2009
DOI: 10.1073/pnas.0905362106
|View full text |Cite
|
Sign up to set email alerts
|

Political partisanship influences perception of biracial candidates' skin tone

Abstract: People tend to view members of their own political group more positively than members of a competing political group. In this article, we demonstrate that political partisanship influences people's visual representations of a biracial political candidate's skin tone. In three studies, participants rated the representativeness of photographs of a hypothetical (Study 1) or real (Barack Obama; Studies 2 and 3) biracial political candidate. Unbeknownst to participants, some of the photographs had been altered to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
133
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(157 citation statements)
references
References 24 publications
21
133
3
Order By: Relevance
“…However, mounting evidence suggests that even perceptions of race are malleable and that biases in race perception have implications for the expression of prejudice. That is, although race is often regarded as fixed and veridically perceived (14), representations of a person's race or ethnicity can shift as a function of the perceiver's social goals and motivations (15)(16)(17)(18)(19). For example, in prior work we found that greater antiegalitarian motives related to the visual perception of African American faces as "Blacker" (20).…”
mentioning
confidence: 96%
“…However, mounting evidence suggests that even perceptions of race are malleable and that biases in race perception have implications for the expression of prejudice. That is, although race is often regarded as fixed and veridically perceived (14), representations of a person's race or ethnicity can shift as a function of the perceiver's social goals and motivations (15)(16)(17)(18)(19). For example, in prior work we found that greater antiegalitarian motives related to the visual perception of African American faces as "Blacker" (20).…”
mentioning
confidence: 96%
“…Research on motivated perception and wishful thinking suggests that ambiguous information tends to be decoded in line with one's goals (e.g., Balcetis & Dunning, 2006;Caruso, Mead, & Balcetis, 2009;Sanford 1936Sanford , 1937. To the extent that people vary in their motivation to forgo a temptation, and to the extent that people's goals shape their interpretation of ambiguous stimuli, it may be that those who are highly motivated to reduce their intake of a temptation are particularly likely to interpret vague postponement as a signal of low valuation for the temptation.…”
Section: Motivation To Forgo the Temptationmentioning
confidence: 99%
“…As a further test of the learning account for the effects of postponement, individual differences in motivation to forgo the temptation were examined. Because ambiguous information tends to be interpreted in line with one's goals (Balcetis & Dunning, 2006;Caruso et al, 2009;Sanford 1936Sanford , 1937, we reasoned that an unspecific postponement intention should be decoded as a signal of low commitment to the temptation particularly among those strongly motivated to give up the temptation. Trait selfcontrol was also measured to show specificity for the moderating effect of motivation to forgo the temptation (i.e., high self-control could be positively or negatively associated with motivation to forgo the temptation).…”
Section: Experiments 3: Consumption Delaymentioning
confidence: 99%
“…This approach does not explore other possible explanations, which presented an opportunity. Therefore, this study extends the research conducted in Caruso et al (2009) in an attempt to test for the presence or absence of inclusion motivation as a mediating influence between like or dislike of the candidate and preference for a lightened, darkened, or unaltered photograph of the candidate. To pursue this end, one of the three experiments conducted in Caruso et al (2009) was replicated and executed using participants from a worker pool provided through mTurk.com.…”
mentioning
confidence: 99%
“…
AbstractIn Caruso et al (2009), the researchers determine that if a participant liked a bi-racial (one black parent and one white parent) male candidate the participant was more inclined to prefer a photograph of him in which he appears to have a lighter complexion. Caruso et al explain the results through the lens of a shade-based account of implicit association.
…”
mentioning
confidence: 99%